2019
DOI: 10.1007/s12576-019-00703-7
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of 5-HT2A receptors inhibits emotional hyperthermia in mice

Abstract: This study determined whether blockade of 5-hydroxytryptamine 2A (5-HT2A) receptors attenuated hyperthermia and tachycardia responses to psychological stress in mice. For this purpose, male mice (C57BL/6N) were pre-instrumented with a telemetric probe to measure core body temperature and heart rate prior to experimentation. Vehicle or 5-HT2A antagonist, eplivanserin hemifumarate (SR-46349B) ((1Z,2E)-1-(2-fluorophenyl)-3-(4-hydroxyphenyl)-2-propen-1-one O-[2-(dimethylamino) ethyl] oxime hemifumarate) (0.5, 1.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…5-HT exerts an inotropic effect on myocardial cells via 5-HT2A (17). Consistent with this, a 5-HT2A antagonist has been shown to be useful in the treatment of overloadinduced heart failure in mice (18). These results suggest the importance of serotonin receptors in heart failure and hypertrophy.…”
Section: Discussionsupporting
confidence: 66%
“…5-HT exerts an inotropic effect on myocardial cells via 5-HT2A (17). Consistent with this, a 5-HT2A antagonist has been shown to be useful in the treatment of overloadinduced heart failure in mice (18). These results suggest the importance of serotonin receptors in heart failure and hypertrophy.…”
Section: Discussionsupporting
confidence: 66%
“…In preclinical modelling studies, 5-HT2AR antagonism impairs acquisition of conditioned defeat (Clinard et al, 2015; Rillich and Stevenson, 2018) and suppresses hyperthermic response to social defeat (Beig et al, 2009; Sinh and Ootsuka, 2019), whereas agonist administration into the basolateral amygdala increases acquisition of conditioned defeat (Clinard et al, 2015). Acute social defeat increases 5-HT levels (Beitia et al, 2005; Gardner et al, 2005; Higuchi et al, 2019; Keeney et al, 2006; Paul et al, 2011), and region-specific increases in 5-HT2AR expression have been found in chronically subordinate animals (Berton et al, 1997; McKittrick et al, 1995).…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
“…The 5-HT2AR also plays a role in body temperature regulation, with agonists reliably increasing core body temperature (Blessing and Seaman, 2003; Friedman and Hirsch, 1971; Klock et al, 1975; Liskow, 1971; Mazzola-Pomietto et al, 1995, Murakami et al, 1980; Pawlyk et al, 2006; Salmi and Ahlenius, 1998) and antagonists blocking this effect (Mazzola-Pomietto et al, 1995; Nisijima et al, 2001). Antagonism of the 5-HT2AR also reduces body temperature (Pawlyk et al, 2006) and blocks hyperthermic response to social defeat (Sinh and Ootsuka, 2019). Some evidence suggests that exposure to heat or cold increases 5-HT levels (Hale et al, 2011; Ishiwata and Greenwood, 2018; Kelly et al, 2011; Myers and Beleslin, 1971), but other studies found no relationship between temperature manipulations and brain 5-HT levels (Ishiwata et al, 2004; Nakagawa et al, 2016; Saito et al, 2005).…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
“…Ootsuka et al [ 189 ] showed that an increase in BAT temperature in rats under restraint stress can be attenuated by selective blockade of 5-HT 2A receptors. Beig et al [ 190 ] and Sinh and Ootsuka [ 191 ] also blocked hyperthermia in social stress models by 5-HT 2A receptor antagonist.…”
Section: 5-ht 2 Receptorsmentioning
confidence: 99%